MiR-122-mediated translational repression of PEG10 and its suppression in human hepatocellular carcinoma. Issue 1 (December 2016) - Shyu, Yu-Chiau; Lee, Tung-Liang; Lu, Mu-Jie; Chen, Jim-Ray; Chien, Rong-Nan; Chen, Huang-Yang; Lin, Ji-Fan; Tsou, Ann-Ping; Chen, Yu-Hsien; Hsieh, Chia-Wen; Huang, Ting-Shuo
Abstract Background Hepatocellular carcinoma (HCC), a primary liver malignancy, is the most common cancer in males and fourth common cancer in females in Taiwan. HCC patients usually have a poor prognosis due to late diagnosis. It has been classified as a complex disease because of the heterogeneous phenotypic and genetic traits of the patients and a wide range of risk factors. Micro (mi)RNAs regulate oncogenes and tumor suppressor genes that are known to be dysregulated in HCC. Several studies have found an association between downregulation of miR-122, a liver-specific miRNA, and upregulation of paternally expressed gene 10 (PEG10) in HCC; however, the correlation between low miR-122 and high PEG10 levels still remains to be defined and require more investigations to evaluate their performance as an effective prognostic biomarker for HCC. Methods An in silico approach was used to isolatePEG10, a potential miR-122 target implicated in HCC development. miR-122S binding sites in thePEG10 promoter were evaluated with a reporter assay. The regulation of PEG10 by miR-122S overexpression was examined by quantitative RT-PCR, western blotting, and immunohistochemistry in miR-122 knockout mice and liver tissue from HCC patients. The relationship between PEG10 expression and clinicopathologic features of HCC patients was also evaluated. Results miR-122 downregulated the expression of PEG10 protein through binding to 3′-untranslated region (UTR) of thePEG10 transcript. In miR-122 knockout mice and HCC patients, the deficiency of miR-122 was associated with HCC progression. The expression of PEG10 was increased in 57.3 % of HCC as compared to paired non-cancerous tissue samples. However, significant upregulation was detected in 56.5 % of patients and was correlated with Okuda stage (P = 0.05) and histological grade (P = 0.001). Conclusions miR-122 suppresses PEG10 expression via direct binding to the 3′-UTR of thePEG10 transcript. Therefore, while PEG10 could not be an ideal diagnostic biomarker for HCC but its upregulation in HCC tissue still has predictive value for HCC prognosis.